Consistency in The Application of Prudential Banking Principles in the Provision of Banking Credit Facilities: Efforts to Prevent Potential Fraud at State-Owned Banks - Amelia, Amelia; Prasetyo, Handoyo (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
State-owned banks play a strategic role in maintaining national economic stability by collecting and distributing public funds. However, lending activities often face the risk of fraud, which can erode public trust and compromise the institution's integrity. This study examines the consistency of applying the principle of prudence in the credit-granting process at state-owned banks and its relevance in preventing fraud. The main issues raised are the continued existence of credit procedure irregularities and weak internal supervision, despite the principle of prudence being clearly regulated in banking regulations. This study aims to analyze how the consistent application of prudential banking principles can prevent potential fraud in the credit-granting process at state-owned banks. The research method employed was a normative juridical approach with a qualitative orientation, involving the collection and analysis of literature reviews through library research, supplemented by interviews with state-owned banks to support the research. The study's results show that fraud often occurs due to weak internal controls, a low culture of compliance, and limited technological infrastructure. The application of prudential banking principles combined with a Good Corporate Governance (GCG) framework, ISO 31000-based risk management, and the support of digital monitoring innovations such as audit trails and early warning systems is intended to strengthen credit risk control. The integration of these policies not only highlights the potential for irregularities but also ensures that credit decisions for prospective borrowers are made in a transparent, accountable manner and in accordance with prudent banking principles.